2020
DOI: 10.1029/2019jd031892
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Reanalysis of Stratospheric Ozone for Trend Studies: Assimilation of the Aura Microwave Limb Sounder and Ozone Mapping and Profiler Suite Limb Profiler Data

Abstract: Compatibility of the stratospheric ozone profile data from the Ozone Mapping and Profiler Suite Limb Profiler (OMPS‐LP) and the Microwave Limb Sounder (MLS) is assessed in the context of a continuity requirement for future reanalyses. A methodology for the assimilation of OMPS‐LP data into the Goddard Earth Observing System data assimilation system with a stratospheric chemistry module is developed. It is demonstrated that a simple homogenization technique significantly reduces the bias between OMPS‐LP and MLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…All observation error covariances were tuned using analysis diagnostics (Desrosiers et al, 2005). As in Wargan et al (2020) the wind, temperature, surface pressure, and tropospheric water vapor are replayed to the MERRA‐2 3‐hourly averaged assimilated fields (GMAO, 2015c) as described in Orbe et al (2017). Lawrence et al (2018) demonstrated that the reanalysis meteorology is suitable for polar processing studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All observation error covariances were tuned using analysis diagnostics (Desrosiers et al, 2005). As in Wargan et al (2020) the wind, temperature, surface pressure, and tropospheric water vapor are replayed to the MERRA‐2 3‐hourly averaged assimilated fields (GMAO, 2015c) as described in Orbe et al (2017). Lawrence et al (2018) demonstrated that the reanalysis meteorology is suitable for polar processing studies.…”
Section: Methodsmentioning
confidence: 99%
“…The data assimilation system used in this work is the GEOS Constituent Data Assimilation System (GEOS CoDAS), a generalization of the carbon monoxide (Tangborn et al, 2009), carbon dioxide (Eldering et al, 2017;Tangborn et al, 2013), and ozone (Wargan et al, 2015(Wargan et al, , 2020 assimilation systems. This work applies GEOS CoDAS to a full stratospheric chemistry model, StratChem (Douglass et al, 1997;Kawa et al, 1995;Nielsen et al, 2017).…”
Section: Data Assimilation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no chemical coupling between GOCART and GEOS-Chem, and no observations are directly assimilated into GEOS-CF. However, stratospheric O 3 in GEOS-Chem is nudged toward O 3 produced by GEOS FP, which is constrained by ozone measurements from the Microwave Limb Sounder (MLS), Ozone Monitoring Instrument (OMI), and NA-SA's Ozone Mapping and Profiler Suite (OMPS) and produces a realistic analysis of O 3 in the stratosphere (Wargan et al, 2015(Wargan et al, , 2020. In addition, near real-time MODIS observations of fire radiative power are used to constrain fire emissions, as produced by the Quick Fire Emissions Dataset (QFED) (Darmenov and Da Silva, 2015).…”
Section: General Descriptionmentioning
confidence: 99%
“…The stratospheric column is then subtracted from EPIC TOZ to obtain tropospheric column ozone. Limb sounders like Aura MLS and OMPS LP have dense samplings and provide an accurate estimate of stratospheric ozone with high vertical resolution (e.g., Hubert et al, 2016;Kramarova et al, 2018;Wargan et al, 2020). These sounders are flown on polarorbiting satellites and make measurements at the same local solar time with ∼14 orbits a day.…”
Section: Epic Tropospheric Ozone Algorithmmentioning
confidence: 99%